Seroprevalence and Risk Factors of Trichinella spiralis Infection in Blood Donors from Western Romania - Radu Pavel; Sorin Ursoniu; Ana Alexandra Paduraru; Rodica Lighezan; Maria Alina Lupu; Tudor Rares Olariu (Medicina, 2022)
Background and Objectives: Trichinellosis, a serious and sometimes fatal human disease, is a foodborne zoonotic disease with worldwide distribution caused by parasitic nematodes of the genus Trichinella. Humans are infected with Trichinella larvae through the ingestion of meat that has not been properly cooked. Romania reported most of the confirmed cases of trichinellosis among the EU countries. The aim of this cross-sectional study was to evaluate, for the first time, the seroprevalence and risk factors of Trichinella infection in blood donors from Western Romania. Materials and Methods: Serum samples of 1347 consecutive blood donors were investigated using an immunoenzymaticassay (ELISA) for the determination of specific IgG class antibodies against T.spiralis. A questionnaire interview was used to obtain information regarding the potential risk factors associated with T. spiralis infection. Mantel–Haenszel chi-squared test or the Fisher exact two-tailed test, as appropriate, were used for comparison between T. spiralis positive and T. spiralis negative blood donors. Student’s t-test was used to evaluate differences between means in studied groups and body mass index was calculated by dividing weight in kilograms by height in meters squared. Statistical analysis was performed using Epi Info Version 7.2 and Stata 16.1. Results: T. spiralis IgG antibodies were detected in 2.00% (27) of 1347 consecutive blood donors. Eating raw and/or undercooked meat, from pigs or wild boars, was found to be the main risk factor (p < 0.001). Strong alcoholic drink consumption was highly associated with T. spiralis infection (p = 0.009). Trichinella seroprevalence was higher among rural residents and males. Subjects identified as Trichinella seropositive were not previously diagnosed and have not been treated for Trichinella infection with any specific therapy. Conclusions: The demonstration of T. spiralis antibodies in healthy blood donors suggests that Trichinella infection may be detected in asymptomatic individuals that were not previously diagnosed with this zoonosis.